Production of a Psyofments Game Oriented Toward High-Level Thinking on the Periodic Table of Elements Material" - Hikmatul Kurnia Azizah; Sari Sari; Riri Aisyah; Oban Sobandi (International Journal of Learning Media on Natural Science (IJLENS), 2025)
This study aims to describe the appearancepsyofments game, analyzing the results of validation tests, and the results of feasibility tests frompsyofments gameoriented towards high-level thinking skills on the material of the periodic system of elements. The research method used isDesign based research (DBR) with the ADDIE approach model which consists of three stages, namely analysis, design, and development. Game psyofmentsthis is an applicationgamesAndroid-based containing questions on the periodic system of elements with different levels of difficulty at each level and oriented towards HOTS questions. The results of the study show that the displaypsyofments gameconsists of a menu selection display, a self-identity column display, a displaystart game, game level display, displayrewardmaterial, and the final score display. The results of the validation test from the validator obtained an average r valuecountfrom all aspects of 0.863 which shows thatpsyofments game This is valid as a learning media in the material of the periodic system of elements. After the media was improved based on the suggestions of the validator, a feasibility test was carried out on 11 students who had studied the material of the periodic system of elements. The results of the feasibility test obtained an average percentage of 90% from all aspects so that it can be concluded thatpsyofments gameoriented towards high-level thinking skills on the material of the periodic system of elements, it is very suitable for use as a learning medium.